Clinical correlates of hypothalamic functional changes in migraine patients. (April 2022) - Messina, Roberta; Rocca, Maria A; Valsasina, Paola; Misci, Paolo; Filippi, Massimo
Objective: To elucidate the hypothalamic involvement in episodic migraine and investigate the association between hypothalamic resting state functional connectivity changes and migraine patients' clinical characteristics and disease progression over the years. Methods: Ninety-one patients with episodic migraine and 73 controls underwent interictal resting state functional magnetic resonance imaging. Twenty-three patients and controls were re-examined after a median of 4.5 years. Hypothalamic resting state functional connectivity changes were investigated using a seed-based correlation approach. Results: At baseline, a decreased functional interaction between the hypothalamus and the parahippocampus, cerebellum, temporal, lingual and orbitofrontal gyrus was found in migraine patients versus controls. Increased resting state functional connectivity between the hypothalamus and bilateral orbitofrontal gyrus was demonstrated in migraine patients at follow-up versus baseline. Migraine patients also experienced decreased right hypothalamic resting state functional connectivity with ipsilateral lingual gyrus. A higher migraine attack frequency was associated with decreased hypothalamic-lingual gyrus resting state functional connectivity at baseline, while greater headache impact at follow-up correlated with decreased hypothalamic-orbitofrontal gyrus resting state functional connectivity at baseline. At follow-up, a lower frequency of migraine attacks was associated with higher hypothalamic-orbitofrontal gyrus resting state functional connectivity. Conclusions: During the interictal phase, the hypothalamus modulates the activity of pain and visual processing areas in episodic migraine patients. The hypothalamic-cortical interplay changes dynamically over time according to patients' clinical features.